Hadis tentang Kejujuran sebagai Spirit untuk Generasi Milenial di Tanah Air - Wafa Salsabila Sakinah; Ilim Abdul Halim; Dadang Darmawan (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the hadith about honesty. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about honesty in Muslim history No. 4721. The results and discussion of this study indicate that the status of quality hadith hasan li ghairihi that meets the qualifications of maqbul ma'mul bih for the practice of Islam. This study concludes that the hadith narrated by Muslim No. 4721 is relevant to be used as a spirit, motivation, actualization of honesty for the millennial generation in the country.